Negative pole piece, secondary battery and electric device

By providing a silicon coating composed of carboxyl polymer and silicon-containing active particles in the negative electrode sheet, the crushing and shedding of the silicon-based negative electrode material in the lithium-ion battery due to volume changes is solved, and the excellent cycle performance of the battery and the reduction of the expansion rate are achieved.

CN119786526AActive Publication Date: 2025-04-08ZHEJIANG LIWINON ELECTRONIC TECHNOLOGY CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411961229.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-08
Estimated Expiration
2044-12-30

AI Technical Summary

Technical Problem

The internal stress caused by volume changes in the silicon-based anode material during lithium embedding and deliquification process leads to the breakage and shedding of the material, affecting the integrity of the electrode and the battery circulation performance.

Method used

The negative electrode sheet is provided with a silicon coating composed of carboxyl polymer, silicon-containing active particles and conductive agent. The silicon coating is located between the current collector and the active substance layer. Through the condensation reaction of the carboxyl polymer and the silicon-containing active particles, a hydrogen bond and ion-dipole interaction are formed to achieve a self-healing effect.

Benefits of technology

By uniformly aligning the silicon material, the expansion of the negative electrode sheet is reduced, the bonding effect between the silicon-containing active particles and the current collector is enhanced, and the circulation performance of the battery is significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119786526A_ABST
    Figure CN119786526A_ABST
Patent Text Reader

Abstract

The invention relates to a negative pole piece, a secondary battery and an electric device, and belongs to the technical field of batteries. The negative pole piece comprises a current collector and a coating arranged on at least one side surface of the current collector, the coating comprises a silicon coating and an active substance coating, and the silicon coating is located between the current collector and the active substance coating; the silicon coating comprises a carboxyl polymer, silicon-containing active particles and a conductive agent; the carboxyl polymer contains-COOM, wherein M is at least one of H, Li, Na and K; and the active substance coating comprises a negative active substance, a conductive agent and a binder. The negative pole piece has low expansion rate in the charge-discharge process, so that the battery has excellent cycle performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of batteries, and in particular relates to a negative electrode sheet, a secondary battery and an electrical device. Background Art

[0002] At present, commercial lithium-ion batteries are mainly composed of carbon-based negative electrodes and lithium transition metal oxide positive electrodes, but the theoretical capacity of carbon-based negative electrodes is limited (for example, the theoretical capacity of graphite negative electrodes is 372mAh / g), which is difficult to meet the needs of high energy density batteries. Compared with carbon-based negative electrodes, the theoretical capacity of silicon-based negative electrodes can reach 4212mAh / g, which is one of the most promising negative electrode materials and can significantly improve the energy density of batteries. However, silicon-based negative electrodes will undergo anisotropic expansion and contraction during the process of lithium insertion and delithiation, with a volume change rate of up to 300%. Due to the huge internal stress caused by the volume change, the silicon material reaches its mechanical limit, eventually breaking and falling off, thereby affecting the integrity of the electrode; at the same time, affected by the interface stress, the active material, conductive agent and current collector lose good contact, resulting in poor battery cycle performance. Summary of the invention

[0003] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a negative electrode plate, a secondary battery and an electrical device.

[0004] To achieve the above object, the technical solution adopted by the present invention is:

[0005] In a first aspect, the present invention provides a negative electrode plate, comprising a current collector and a coating disposed on at least one side of the current collector; the coating comprises a silicon coating and an active material coating, and the silicon coating is located between the current collector and the active material coating;

[0006] The silicon coating comprises a carboxyl polymer, silicon-containing active particles and a conductive agent;

[0007] The carboxyl polymer comprises -COOM, wherein M is at least one of H, Li, Na, and K;

[0008] The active material coating layer includes a negative electrode active material, a conductive agent and a binder.

[0009] As an embodiment of the present invention, the mass proportion of the carboxyl polymer in the silicon coating is 1% to 10%.

[0010] As an embodiment of the present invention, the molar percentage of -COOM in the carboxyl polymer is 50% to 70%.

[0011] As an embodiment of the present invention, the chemical structural formula of the carboxyl polymer is:

[0012]

[0013] Wherein, M is at least one of H, Li, Na, and K;

[0014] R1, R2, and R3 are independently selected from at least one of H, C1-C3 straight chain or branched alkyl;

[0015] m1, m2 and m3 satisfy: 50%≤m1 / (m1+m2+m3)≤70%.

[0016] As an embodiment of the present invention, the silicon-containing active particles include at least one of nano-silicon, silicon oxide, and silicon carbon.

[0017] As an embodiment of the present invention, the mass proportion of the silicon coating in the coating is 2% to 5%.

[0018] As an embodiment of the present invention, the negative electrode active material includes graphite, or a mixture of graphite and at least one of nano-silicon, silicon oxide, and silicon carbon.

[0019] As an embodiment of the present invention, the average thickness of the coating layer is 25-40 μm.

[0020] In a second aspect, the present invention provides a secondary battery, which includes the above-mentioned negative electrode plate.

[0021] In a third aspect, the present invention provides an electrical device, which includes the above-mentioned secondary battery, and the secondary battery serves as a power supply for the electrical device.

[0022] Compared with the prior art, the present invention has the following beneficial effects:

[0023] The present invention arranges a silicon coating mainly composed of a carboxyl polymer, silicon-containing active particles and a conductive agent between the current collector and the active material layer in the negative electrode sheet, so that the silicon is evenly arranged in the entire negative electrode sheet and located in the same direction, thereby making the overall expansion of the negative electrode sheet more uniform during the charge and discharge process, thereby reducing the expansion of the negative electrode sheet; moreover, the carboxyl groups on the molecular chains of the carboxyl polymer in the silicon coating can undergo condensation reactions with the hydroxyl groups on the surface oxide layer of the silicon-containing active particles to form hydrogen bonds and ion-dipole interactions, thereby achieving a self-healing effect in the expansion and contraction process of the negative electrode sheet; at the same time, the carboxyl polymer contains side chain groups, which can have multi-dimensional contact with the silicon-containing active particles, thereby preventing the molecular chain from slipping to effectively limit the movement of the silicon-containing active particles, thereby greatly enhancing the bonding effect between the silicon-containing active particles and the current collector, reducing the bonding failure between the silicon-containing active particles and the current collector, and giving the battery excellent cycle performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1Schematic diagram of the structure of the negative electrode plate in Example 1. DETAILED DESCRIPTION

[0025] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments and comparative examples, the purpose of which is to understand the content of the present invention in detail, rather than to limit the present invention. All other embodiments obtained by those of ordinary skill in the art without making creative work premise belong to the protection scope of the present invention. The experimental reagents and instruments involved in the implementation of the present invention, unless otherwise specified, are all commonly used common reagents and instruments.

[0026] According to a first aspect of the present invention, there is provided a negative electrode sheet, comprising a current collector and a coating provided on at least one side of the current collector; the coating comprises a silicon coating and an active material coating, and the silicon coating is located between the current collector and the active material layer;

[0027] The silicon coating comprises a carboxyl polymer, silicon-containing active particles and a conductive agent;

[0028] The carboxyl polymer comprises -COOM, wherein M is at least one of H, Li, Na, and K;

[0029] The active material coating layer includes a negative electrode active material, a conductive agent and a binder.

[0030] The present invention arranges a silicon coating mainly composed of a carboxyl polymer, silicon-containing active particles and a conductive agent between the current collector and the active material layer in the negative electrode sheet, so that the silicon is evenly arranged in the entire negative electrode sheet and located in the same direction, thereby making the overall expansion of the negative electrode sheet more uniform during the charge and discharge process, thereby reducing the expansion of the negative electrode sheet; moreover, the carboxyl groups on the molecular chains of the carboxyl polymer in the silicon coating can undergo condensation reactions with the hydroxyl groups on the surface oxide layer of the silicon-containing active particles to form hydrogen bonds and ion-dipole interactions, thereby achieving a self-healing effect in the expansion and contraction process of the negative electrode sheet; at the same time, the carboxyl polymer contains side chain groups, which can have multi-dimensional contact with the silicon-containing active particles, thereby preventing the molecular chain from slipping to effectively limit the movement of the silicon-containing active particles, thereby greatly enhancing the bonding effect between the silicon-containing active particles and the current collector, reducing the bonding failure between the silicon-containing active particles and the current collector, and giving the battery excellent cycle performance.

[0031] Optionally, the carboxyl polymer is polymerized from acrylic acid monomers, acrylamide monomers and acrylonitrile monomers.

[0032] Optionally, the conductive agent in the silicon coating includes but is not limited to at least one of graphite, acetylene black, carbon black, carbon nanotubes, carbon fibers, etc.

[0033] Optionally, the conductive agent in the active material coating includes but is not limited to at least one of graphite, acetylene black, carbon black, carbon nanotubes, carbon fibers, etc.; the binder includes but is not limited to at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), carboxymethyl cellulose (CMC), styrene-butadiene rubber (SBR), polyurethane (PU), polyvinyl alcohol (PVA), polyvinyl butyral (PVB), etc.

[0034] As an embodiment of the present invention, the mass proportion of the carboxyl polymer in the silicon coating is 1% to 10%. Optionally, the mass proportion of the carboxyl polymer in the silicon coating can be 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10% or any two of the range values. Studies have found that the carboxyl polymer with the above mass proportion can not only provide excellent adhesion to effectively prevent the silicon coating from peeling off from the current collector, but also maintain a low impedance, thereby significantly improving the cycle performance of the battery.

[0035] As an embodiment of the present invention, the molar percentage of -COOM in the carboxyl polymer is 50% to 70%. Optionally, the molar percentage of -COOM in the carboxyl polymer can be any one of 50%, 55%, 60%, 65%, 70% or any two of the range values. Studies have found that carboxyl polymers containing the above molar percentage of -COOM can provide suitable intermolecular forces to ensure excellent bonding properties, which is beneficial to improving the cycle performance of the battery.

[0036] As an embodiment of the present invention, the chemical structural formula of the carboxyl polymer is:

[0037]

[0038] Wherein, M is at least one of H, Li, Na, and K;

[0039] R1, R2, and R3 are independently selected from at least one of H, C1-C3 straight chain or branched alkyl;

[0040] m1, m2 and m3 satisfy: 50%≤m1 / (m1+m2+m3)≤70%.

[0041] The carboxyl groups in the M1 block compound can undergo condensation reactions with the hydroxyl groups on the surface oxide layer of the silicon-containing active particles to form hydrogen bonds and ion-dipole interactions, thereby enabling the negative electrode to achieve a self-healing effect during expansion and contraction.

[0042] The M2 block compound can make multi-dimensional contact with the silicon-containing active particles, thereby preventing the molecular chain from slipping and effectively restricting the movement of the silicon-containing active particles, thereby greatly enhancing the bonding effect between the silicon-containing active particles and the current collector;

[0043] The nitrile group in the M3 block compound can enhance the ionic conductivity in the binder, thereby improving the electrochemical performance.

[0044] As an embodiment of the present invention, the silicon-containing active particles include at least one of nano-silicon, silicon oxide, and silicon carbon.

[0045] As an embodiment of the present invention, the mass proportion of the silicon coating in the coating is 2% to 5%. Optionally, the mass proportion of the silicon coating in the coating can be any one of 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, or any two of them. Studies have found that when the mass proportion of the silicon coating is 2% to 5%, it is not only conducive to coating to form a uniform silicon coating, but also enables the carboxyl polymer to better restrain the silicon coating, avoid excessive expansion of the silicon coating and delamination, thereby making the battery have better cycle performance.

[0046] As an embodiment of the present invention, the negative electrode active material includes graphite, or a mixture of graphite and at least one of nano-silicon, silicon oxide, and silicon carbon. Preferably, the mass proportion of graphite in the negative electrode active material is ≥50%, preferably 90% to 100%; specifically, it can be 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, 95%, etc.

[0047] As an embodiment of the present invention, the average thickness of the coating is 25-40 μm. Optionally, the average thickness of the coating can be any one or any two of 25 μm, 27 μm, 30 μm, 33 μm, 35 μm, 38 μm, and 40 μm.

[0048] In a second aspect, the present invention provides a secondary battery, which includes the above-mentioned negative electrode plate.

[0049] In a third aspect, the present invention provides an electrical device, which includes the above-mentioned secondary battery, and the secondary battery serves as a power supply for the electrical device.

[0050] In order to clearly understand the technical solution of the present invention, the present invention is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed by the present invention.

[0051] The AMN polymer (chemical structure is shown in formula (I), wherein M, R1, R2 and R3 are all H) is obtained by free radical polymerization of acrylic acid monomer, acrylamide monomer and acrylonitrile monomer. The molar percentage of carboxyl groups in the AMN polymer is regulated by adjusting the amount of acrylic acid monomer.

[0052]

[0053] Example 1

[0054] This embodiment provides a negative electrode sheet, and the preparation method thereof comprises the following steps:

[0055] S1, a carboxyl polymer (AMN polymer, wherein the molar percentage of carboxyl is 60% (i.e., m1 / (m1+m2+m3)=60%, m1:m2:m3=6:2:2)), silicon-containing active particles (silicon carbon), a conductive agent (CNT), and a solvent (deionized water) are uniformly mixed to obtain a coating slurry 1 (wherein the mass ratio of silicon-containing active particles, carboxyl polymer and conductive agent is 90:5:5);

[0056] The negative electrode active material (graphite), thickener (CMC), conductive agent (Super-P), binder (SBR) and solvent (deionized water) were uniformly mixed to obtain coating slurry 2 (wherein the mass ratio of the negative electrode active material, thickener, conductive agent and binder was 95:2:2:1);

[0057] S2. Coat the coating slurry 1 in S1 on both sides of the copper foil, and dry it to form a silicon coating; then coat the coating slurry 2 in S1 on the surface of the silicon coating, and dry it to form an active material layer to obtain a negative electrode sheet (wherein the mass proportion of the silicon coating in the coating (i.e., silicon coating + active material layer) is 2%).

[0058] It has been measured that the average thickness of the coating in the negative electrode sheet is 30μm.

[0059] Example 2

[0060] This embodiment provides a negative electrode plate, and its preparation method is basically the same as that of Embodiment 1, except that: in step S2, the mass proportion of the silicon coating in the coating of the negative electrode plate is 3%.

[0061] Example 3

[0062] This embodiment provides a negative electrode plate, and its preparation method is basically the same as that of Embodiment 1, except that: in step S2, the mass proportion of the silicon coating in the coating of the negative electrode plate is 4%.

[0063] Example 4

[0064] This embodiment provides a negative electrode plate, and its preparation method is basically the same as that of Embodiment 1, except that: in step S2, the mass proportion of the silicon coating in the coating of the negative electrode plate is 5%.

[0065] Example 5

[0066] This embodiment provides a negative electrode plate, and its preparation method is basically the same as that of Embodiment 1, except that: in step S1, the mass ratio of silicon-containing active particles, carboxyl polymer and conductive agent in the coating slurry 1 is 94:1:5.

[0067] Example 6

[0068] This embodiment provides a negative electrode plate, and its preparation method is basically the same as that of Embodiment 1, except that: in step S1, the mass ratio of silicon-containing active particles, carboxyl polymer and conductive agent in the coating slurry 1 is 85:10:5.

[0069] Example 7

[0070] This embodiment provides a negative electrode plate, and its preparation method is basically the same as that of Example 1, except that: the carboxyl polymer in the coating slurry 1 in step S1 is an AMN polymer, in which the molar percentage of the carboxyl group is 50% (i.e., m1 / (m1+m2+m3)=50%, m1:m2:m3=5:2:3).

[0071] Example 8

[0072] This embodiment provides a negative electrode plate, and its preparation method is basically the same as that of Example 1, except that the carboxyl polymer in the coating slurry 1 in step S1 is an AMN polymer, in which the molar percentage of the carboxyl group is 70% (i.e., m1 / (m1+m2+m3)=70%, m1:m2:m3=7:1:2).

[0073] Example 9

[0074] This embodiment provides a negative electrode plate, and its preparation method is basically the same as that of Embodiment 1, except that: the silicon-containing active particles in the coating slurry 1 in step S1 are silicon oxide.

[0075] Example 10

[0076] This embodiment provides a negative electrode plate, and its preparation method is basically the same as that of Embodiment 1, except that: in step S1, the negative electrode active material in the coating slurry 2 is composed of graphite and silicon carbon in a mass ratio of 90:10.

[0077] Comparative Example 1

[0078] This comparative example provides a negative electrode sheet, and its preparation method is basically the same as that of Example 1, except that step S2 is:

[0079] S2. Evenly mix the coating slurry 1 and the coating slurry 2 in S1 (satisfying a / (a+b)=2%, a is the total mass of the carboxyl polymer, silicon-containing active particles and conductive agent in the coating slurry 1, and b is the total mass of the negative electrode active material, thickener, conductive agent and binder in the coating slurry 2) to obtain a mixed slurry; then coat the mixed slurry on both sides of the copper foil, dry it to form a coating, and obtain a negative electrode sheet.

[0080] Comparative Example 2

[0081] This comparative example provides a negative electrode plate, and its preparation method is basically the same as that of Example 1, except that: in step S1, the molar percentage of carboxyl in the carboxyl polymer AMN polymer in the coating slurry 1 is 100%, and the chemical structural formula of the carboxyl polymer is:

[0082]

[0083] Comparative Example 3

[0084] This comparative example provides a negative electrode sheet, and its preparation method is basically the same as that of Example 1, except that: the carboxyl polymer AMN polymer in the coating slurry 1 in step S1 has no carboxyl group, wherein m2:m3=1:1, and the chemical structure of the carboxyl polymer is:

[0085]

[0086] Comparative Example 4

[0087] This comparative example provides a negative electrode sheet, and the preparation method thereof is as follows:

[0088] S1, a carboxyl polymer (AMN polymer, wherein the molar percentage of carboxyl is 60% (i.e., m1 / (m1+m2+m3)=60%, m1:m2:m3=6:2:2)), silicon-containing active particles (silicon carbon), a negative electrode active material (graphite), a conductive agent (CNT) and a solvent (deionized water) are uniformly mixed to obtain a coating slurry (wherein the mass ratio of silicon-containing active particles, negative electrode active material graphite, carboxyl polymer and conductive agent is 1.8:93.1:2:3.1, wherein the ratio of silicon-containing active particles and negative electrode active material graphite is the same as that in Example 1);

[0089] S2, coating the coating slurry in S1 on both sides of the surface of the copper foil, drying to form an active material layer, and obtaining a negative electrode sheet.

[0090] Performance Testing

[0091] The negative electrode sheets in the embodiments and comparative examples are stacked in order with the positive electrode sheets and the separator, so that the separator (PE film) is located between the positive and negative electrode sheets. A bare battery cell is obtained after welding, winding and hot pressing. The bare battery cell is placed in an outer packaging aluminum-plastic film and baked in an oven at 85±5°C for 24 hours. The electrolyte is injected into the dried battery, allowed to stand, formed and divided to obtain a lithium-ion soft-pack battery.

[0092] The preparation of the above-mentioned positive electrode sheet includes the following steps: mixing the positive electrode active material lithium cobalt oxide, the conductive agent acetylene black, the conductive agent CNT and the adhesive PVDF according to a mass ratio of 98:0.5:0.7:0.8, adding them to N-methylpyrrolidone (NMP) and stirring them thoroughly to form a positive electrode slurry with a solid content of 76%, and then coating the positive electrode slurry on aluminum foil, drying, rolling and cutting to obtain a positive electrode sheet.

[0093] The electrolyte is a 1 mol / L LiPF6 solution, wherein the solvent is composed of EP:EC:DEC in a volume ratio of 4:3:3.

[0094] The above-mentioned lithium-ion soft-pack battery is subjected to performance testing, and the specific testing method is as follows:

[0095] 1) Capacity retention rate: The lithium-ion battery is repeatedly charged and discharged through the following steps, and the cycle capacity retention rate of the lithium-ion battery is calculated. First, the first charge and discharge are performed in an environment of 25°C, and constant current and constant voltage charging is performed at a charging current of 0.1C (i.e., the current value of the theoretical capacity is completely discharged within 10 hours) until the upper limit voltage is 4.53V, and then constant current discharge is performed at a discharge current of 1C until the final voltage is 3V, and the discharge capacity of the first cycle is recorded; then 200 charge and discharge cycles are performed, and the discharge capacity of the 200th cycle is recorded. Cycle capacity retention rate = (discharge capacity of the 200th cycle / discharge capacity of the first cycle) × 100%.

[0096] 2) Volume expansion rate: The lithium-ion secondary battery is repeatedly charged and discharged through the following steps, and the cycle expansion rate of the lithium-ion battery is calculated. First, the initial thickness of the battery is measured at room temperature, and then, after 200 constant current charge and discharge at a discharge current of 1C (i.e., the current value that completely discharges the theoretical capacity within 1 hour) at 25°C, the battery is fully charged to 4.53V, and the battery thickness after the 200th cycle is measured. Cycle expansion rate = (battery thickness after the 200th cycle - initial thickness before cycling) / initial thickness before cycling × 100%.

[0097] Table 1 Performance of lithium-ion soft-pack batteries assembled with negative electrode sheets in various embodiments and comparative examples

[0098] serial number Capacity retention rate / % Volume expansion rate / % Example 1 95.4% 8.9% Example 2 94.8% 10.1% Example 3 93.1% 12.5% Example 4 89.7% 14.6% Example 5 90.7% 13.6% Example 6 91.9% 12.3% Example 7 91.4% 13.4% Example 8 90.2% 12.9% Example 9 89.6% 14.3% Example 10 86.8% 15.1% Comparative Example 1 70.7% 21.9% Comparative Example 2 79.5% 17.4% Comparative Example 3 72.7% 20.3% Comparative Example 4 68.7% 23.6%

[0099] According to the data in Table 1, the capacity retention rate of the lithium-ion soft-pack batteries of Examples 1 to 10 after 200 cycles is all above 85%, and the volume expansion rate is all ≤16%, indicating that the negative electrode plate of the present invention has a lower expansion rate, which can make the battery have excellent cycle performance.

[0100] By comparing Example 1 with Comparative Example 1, it can be seen that the double-layer coating of pure silicon base coating and active material layer can significantly improve the capacity retention rate and cycle expansion rate. Placing silicon between the current collector and the active material layer can make the silicon evenly arranged in the entire negative electrode sheet and located in the same direction, thereby making the overall expansion of the negative electrode sheet during the charge and discharge process more uniform, thereby reducing the expansion of the negative electrode sheet.

[0101] By comparing Examples 1 to 10 with Comparative Example 4, it is found that the conventional Si-C negative electrode easily causes uneven distribution of silicon in the electrode piece, thereby causing excessive local expansion of the battery cell, deformation of the battery, and ultimately increasing cycle expansion.

[0102] By comparing Examples 1, 7, and 8 with Comparative Examples 2 to 3, it can be seen that the carboxyl group has the best performance in the range of 50% to 70%. If there are more carboxyl groups and fewer other groups, the multidimensional contact between the silicon-containing active particles will be reduced. At the same time, the role of other groups in preventing the silicon-containing active particles from sliding sideways between molecules will be weakened. If there are no carboxyl groups, the hydrogen bonding effect between molecules will be reduced, resulting in poor adhesion between the silicon-containing active particles and the current collector, and ultimately causing poor battery performance.

[0103] By comparing Examples 1 to 4, it is found that the greater the proportion of the silicon base coating, the greater the cycle expansion. This is mainly because the greater the proportion of the silicon base coating, the greater the overall silicon content, and the cumulative effect formed in the expansion direction will cause the battery cell to expand larger.

[0104] By comparing Examples 1, 5, and 6, the mass ratio of silicon-containing active particles, carboxyl polymers, and conductive agent is 90:5:5, and the best performance is achieved. When the proportion of carboxyl polymers is relatively small, the binding effect on the silicon-containing active particles is weakened; when the proportion of carboxyl polymers is relatively large, lithium deposition in the battery will occur locally, and the cycle expansion will increase.

[0105] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A negative electrode plate, characterized in that: It comprises a current collector and a coating disposed on at least one side of the current collector; the coating comprises a silicon coating and an active material coating, and the silicon coating is located between the current collector and the active material coating; The silicon coating comprises a carboxyl polymer, silicon-containing active particles and a conductive agent; The carboxyl polymer comprises -COOM, wherein M is at least one of H, Li, Na, and K; The active material coating layer includes a negative electrode active material, a conductive agent and a binder.

2. The negative electrode sheet according to claim 1, characterized in that: The mass proportion of the carboxyl polymer in the silicon coating is 1% to 10%.

3. The negative electrode sheet according to claim 2, characterized in that: The molar percentage of -COOM in the carboxyl polymer is 50% to 70%.

4. The negative electrode sheet according to claim 2, characterized in that: The chemical structural formula of the carboxyl polymer is: Wherein, M is at least one of H, Li, Na, and K; R1, R2, and R3 are independently selected from at least one of H, C1-C3 straight chain or branched alkyl; m1, m2 and m3 satisfy: 50%≤m1 / (m1+m2+m3)≤70%.

5. The negative electrode sheet according to claim 1, characterized in that: The silicon-containing active particles include at least one of nano-silicon, silicon oxide, and silicon carbon.

6. The negative electrode sheet according to claim 1, characterized in that: The mass proportion of the silicon coating in the coating is 2% to 5%.

7. The negative electrode sheet according to claim 1, characterized in that: The negative electrode active material includes graphite, or a mixture of graphite and at least one of nano silicon, silicon oxide, and silicon carbon.

8. The negative electrode sheet according to claim 1, characterized in that: The average thickness of the coating is 25-40 μm.

9. A secondary battery, characterized in that: The invention comprises the negative electrode sheet as described in any one of claims 1 to 8.

10. An electrical device, characterized in that: The secondary battery according to claim 9 is included, and the secondary battery is used as a power supply for the electrical device.

Citation Information

Patent Citations

  • Negative pole piece of lithium ion battery, and lithium ion battery using the negative pole piece

    CN109585781A

  • Negative pole piece and electrochemical device comprising same

    CN114094041A

  • Negative pole piece and electrochemical device

    CN115966653A

  • Negative plate, preparation method thereof and secondary battery

    CN117038857A

  • Silicon-based negative pole piece, preparation method and lithium ion battery

    CN118507734A